2014
DOI: 10.3174/ajnr.a3890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gadolinium Contrast Agent Administration on Automatic Brain Tissue Classification of Patients with Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:The administration of gadolinium contrast agent is a common part of MR imaging examinations in patients with MS. The presence of gadolinium may affect the outcome of automated tissue classification. The purpose of this study was to investigate the effects of the presence of gadolinium on the automatic segmentation in patients with MS by using the synthetic tissue-mapping method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…As an example, the ICV could be defined as either the intracranial cavity measured directly [42] or as the sum of the volumes of GM, WM and CSF [43]. Only studies having included the complete intracranial space in the assessment of ICV were included in the aggregated statistical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the ICV could be defined as either the intracranial cavity measured directly [42] or as the sum of the volumes of GM, WM and CSF [43]. Only studies having included the complete intracranial space in the assessment of ICV were included in the aggregated statistical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Future technical effort should try to eliminate the need for this gap in SyMRI and should try to make high-resolution 3D acquisitions possible, which is increasingly important in MS studies. 30,31 Previous studies of the effects of intravenous gadoliniumbased contrast media on the volumetric output of SyMRI indicate that it is important to consistently acquire synthetic MR imaging either pre-or postcontrast for comparability 32 ; these findings are the reason we chose to focus on nonenhanced acquisitions in this study. Future studies will be able to clarify how synthetic MR imaging could be implemented as a postcontrast examination and in a longitudinal fashion in MS.…”
Section: Discussionmentioning
confidence: 99%
“…GdCl 3 is an MRI contrast agent which is widely used at present and whose safety has been evaluated (27,28). We found that high dosages of GdCl 3 markedly suppressed the proliferation of macrophages.…”
Section: Discussionmentioning
confidence: 98%